Inhibition of AcrB efflux pump in multidrug-resistant gram-negative bacteria by herbal extracts - Florida Tilton; Shanmughasundar D; Aneesh Nair; Bindu D; Chitralekha Saikumar; Johnson WMS (International Journal of Research in Pharmaceutical Sciences, 2023)
The emergence of multidrug-resistant gram-negative bacteria has increased drastically over the years contributing to therapeutic failures. Mechanisms which modify the membrane permeation processes, such as increased efflux pump activity or decreased influx of antibiotics, are the major contributors of multidrug resistance in bacterial phenotype. Many approaches from different perspectives are being developed and applied in clinical and research to overcome this threat. Antibiotic resistance can be encountered by introducing more powerful antibiotics that kill the bacterial cells more effectively, by using new therapeutic compounds or by eliminating one or more of the mechanisms of resistance by resistance modifying agents. Herbal plants synthesise a wide variety of compounds that are antibacterial or inhibit the activity of efflux pump (EPI) in nature. This study involves the analysis of efflux pump inhibitory activities of herbal extracts and comparison of their synergetic effect with antibiotics which would have a new approach to counter antibiotic resistance.